KNOWLEDGE, ATTITUDE AND PRACTICE ABOUT HYPERTENSIVE GESTATIONAL SYNDROME AMONG PREGNANT WOMEN: A RANDOMIZED CLINICAL TRIAL. - da Silva Jacob, Lia Maristela; Mafetoni, Reginaldo Roque; Baena de Moraes Lopes, Maria Helena; Kakuda Shimo, Antonieta Keiko (Texto & Contexto Enfermagem, 2022)
Objective: to evaluate knowledge, attitude and practice about Gestational Hypertensive Syndrome among pregnant women, after an educational intervention. Method: a controlled, randomized and longitudinal clinical trial, related to the Knowledge, Attitude and Practice survey on Gestational Hypertensive Syndrome complications, carried out with 120 pregnant women at a public maternity hospital in Fortaleza-CE, Brazil. Data collection was performed at three moments and the pregnant women were separated into two groups with 60 participants each. For quantitative comparisons, the Student's t test or the Mann-Whitney's test were applied. To study qualitative associations, the Chi-square or Fisher's exact tests were employed. Results: adequate assessment of knowledge, attitude and practice was identified in the intervention group, on the seventh and thirtieth days after the intervention (p<0.05), with an increased chance of adequate knowledge on the seventh (Odds Ratio=6.63 - Confidence Interval: 3.5-12.55) and on the thirtieth (Odds Ratio=6.25 - Confidence Interval: 3.13-12.50) days. In this group, the attitude was adequate on the seventh (Odds Ratio=6.11 - Confidence Interval: 3.28-11.39) and on the thirtieth (Odds Ratio=6.44 - Confidence Interval: 3.49-11.89) days. The practice was also adequate on the seventh (Odds Ratio=3.73 - Confidence Interval: 2.21-6.28) and on the thirtieth (Odds Ratio=4.91 - Confidence Interval: 2.90-8.32) days. Conclusion: the pregnant women who participated in the educational intervention presented more adequacy in relation to knowledge, attitude and practice, when compared to those in the control group. Brazilian Registry of Clinical Trials (Registro Brasileiro de Ensaios Clínicos, REBEC) RBR-8wyp8j